The role of palaeoecology in reconciling biodiversity conservation, livelihoods and carbon storage in Madagascar - Gillson, Lindsey; Razanatsoa, Estelle; Razafimanantsoa, Andriantsilavo Hery Isandratana; Virah-Sawmy, Malika; Ekblom, Anneli (Frontiers in Conservation Science, 2023)
Planting trees is proposed as an important climate mitigation tool, but can be detrimental to biodiversity and livelihoods if not carefully, planned and managed, with landscape history and livelihoods in mind. In Madagascar, deforestation is of concern, and a threat to forest-adapted biota. However, much of Madagascar’s landscape harbours ancient mosaic and open ecosystems that are home to unique suites of flora and fauna and provide a wide range of ecosystem services. Though guidelines of ecologically and socially responsible reforestation are emerging, the potential role of landscape history and palaeoecology has been generally underemphasised. Here, using Madagascar as a case study, we argue that forest restoration projects need a sound understanding of landscape history that includes a greater integration of palaeoecological data. This would help establish the former composition and extent of forests and also investigate the antiquity of open and mosaic ecosystems. When economic interests are strong, information from palaeoecology and environmental history can help reduce biases when identifying appropriate locations and suites of species for forestation. Furthermore, a reflective approach to landscape history can contribute to restoration projects that integrate cultural and livelihood considerations. A transdisciplinary approach that considers local needs and cultural context can facilitate the design and implementation of restoration projects that share benefits equitably. Underpinning this ambition is a more comprehensive and accurate consideration of ecosystem service benefits in a changing climate that includes accurate carbon storage calculations, as well as other ecosystem services including water provision, soil formation and erosion prevention, grazing resources, medicine and cultural components.